New technologies and languages ​​in communication - Blanco-López, Desiderio (1988)
Most of the conferences, seminars and meetings that have taken place in the 80s on social communication have been devoted to the topic of new technologies. Looking through the annals of such events we can see that the reflection has focused on the social, political and cultural effects that new technologies trigger in social life, as well as on the meticulous description of these technologies.